Do Executive Functions Predict Written Composition?: Effects beyond Age, Verbal Intelligence and Reading Comprehension - Arán Filippetti, Vanessa (2015)
Background: Several studies have revealed the importance of executive functioning processes for school learning. However, research examining which specific executive functions (EFs) can influence written expression is scarce. This work aimed at i) analyzing the relationship between different EF tasks and different writing tasks (writing a narrative text vs. writing an expository text) and ii) studying which EFs account for unique variance in the composition of written texts, after controlling for age, verbal intelligence (verbal IQ) and reading comprehension.Material/Methods: A total of 186 8-to 15-year old children and adolescents were measures of EF, verbal IQ, reading, and writing abilities (i.e., narrative text and expository text). Pearson´s correlations and hierarchical multiple regression analysis were used.Results: Domain-specific associations were found between the executive components and the different writing tasks. Hierarchical regressions analysis indicated that only Working Memory (WM) and spontaneous flexibility (i.e., verbal fluency) significantly accounted for variance in the production of a narrative text (r2 = .13, p < .001), whereas specific tasks that measure spontaneous flexibility (i.e., verbal and non-verbal fluency), WM and inhibition, explained a percentage of the variance in the composition of an expository text (r2 = .24, p < .001).Conclusions: The results support the hypothesis that EF contributes to academic performance in school-age children and highlights the importance of considering EF as a process that contributes to written composition.